3D printing integral photocatalytic material as well as preparation method and application thereof

By combining BiOBr with RGO and using 3D printing technology to form a three-dimensional composite structure, the limitations of existing photocatalysts in terms of visible light utilization and electron-hole pair separation efficiency are solved, and efficient degradation of organic pollutants such as levofloxacin is achieved, with significant technical advantages and environmental friendliness.

CN119746892APending Publication Date: 2025-04-04ANHUI NORMAL UNIV

Patent Information

Application Number
CN202411881332.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing photocatalysts have limitations in the utilization of visible light and the separation efficiency of electron-hole pairs, and it is difficult to efficiently degrade organic pollutants such as antibiotics such as levofloxacin in water.

Method used

By combining the two-dimensional photocatalytic material BiOBr with RGO with good conductivity, a three-dimensional composite structure is formed using 3D printing technology to increase the specific surface area and active sites of the material, promote the separation and transmission of photogenerated charges, thereby improving the rate and efficiency of photocatalytic reactions.

Benefits of technology

It significantly improves the photocatalytic efficiency, especially in the treatment of low-concentration pollutants, which can efficiently degrade organic pollutants such as levofloxacin, and is simple to operate, low cost, and has good stability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746892A_ABST
    Figure CN119746892A_ABST
Patent Text Reader

Abstract

The invention provides a 3D printing integral photocatalytic material and a preparation method and application thereof.The preparation method includes the steps that polyvinylpyrrolidone is used as a template agent, and ultrathin BiOBr nanosheets are synthesized through a hydrothermal method; and then carrying out reduction mixing on the ultrathin BiOBr nanosheet, graphene oxide GO and hydrazine hydrate, and carrying out 3D printing after a reaction to obtain the A-BiOBr / RGO composite material. Compared with the prior art, the composite material disclosed by the invention shows excellent performance of photocatalytic degradation of pollutants (LEV) in water under visible light, and can be applied to a PES film and a PMR reactor. The preparation method of the catalyst is simple and easy to operate, has good stability and environmental friendliness, is easy to recycle, and has remarkable technical advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of environmental protection, water treatment and material preparation, and in particular to a 3D printed integral photocatalytic material and a preparation method and application thereof, for treating wastewater containing antibiotics such as levofloxacin (LEV) and other organic micropollutants. Background Art

[0002] In water treatment technology, photocatalytic degradation is a process that uses light energy to excite semiconductor materials to generate electron-hole pairs, which in turn trigger redox reactions to decompose organic pollutants. Photocatalytic technology is seen as a promising solution due to its high efficiency and environmentally friendly characteristics. However, existing photocatalysts, such as bismuth oxybromide (BiOBr), have limitations in visible light utilization and electron-hole pair separation efficiency.

[0003] In the prior art, the Chinese invention patent with publication number CN 116251627 A published on June 13, 2023, discloses a rapid microwave preparation method for bismuth oxybromide photocatalyst, and the disclosed preparation method is: a certain amount of potassium bromide and bismuth nitrate are dissolved in water and acetic acid solution respectively, and magnetically stirred until completely dissolved to obtain potassium bromide solution and bismuth nitrate acetic acid solution; potassium bromide solution is added dropwise to bismuth nitrate acetic acid solution, and then magnetically stirred for 30 minutes after dropwise addition to obtain a mixed suspension; then the mixed suspension is placed in a microwave reactor for complete reaction; after the reaction is completed, it is cooled to room temperature for centrifugal washing and dried to obtain a bismuth oxybromide photocatalyst. However, its photocatalytic performance is limited, and it only discloses the degradation of rhodamine B organic dye, and is not disclosed for the degradation of other organic pollutants.

[0004] Organic pollutants in water, especially antibiotics such as levofloxacin (LEV), have become a global environmental problem due to their resistance to degradation and environmental persistence. Conventional water treatment technologies are inefficient and costly in removing these trace-level pollutants.

[0005] Therefore, it is necessary to provide a photocatalyst with enhanced photocatalytic performance for the photocatalytic degradation of levofloxacin. Summary of the invention

[0006] The present invention provides a 3D printed monolithic photocatalytic material and a preparation method thereof. The present invention combines a two-dimensional photocatalytic material BiOBr with RGO having good conductivity, forms a three-dimensional composite structure through 3D printing, increases the specific surface area of ​​the material, provides more active sites, and promotes the separation and transmission of photogenerated charges, thereby improving the rate and efficiency of the photocatalytic reaction. The preparation method is simple and low in cost.

[0007] Another object of the present invention is to provide an application of a 3D printed monolithic photocatalytic material for degrading organic pollutants, especially low-concentration degradation of levofloxacin antibiotics (LEV).

[0008] The specific technical solutions of the present invention are as follows:

[0009] A method for preparing a 3D printed monolithic photocatalytic material comprises the following steps:

[0010] 1) Ultrathin BiOBr nanosheets were synthesized by hydrothermal method using polyvinyl pyrrolidone as template;

[0011] 2) Ultrathin BiOBr nanosheets are mixed with graphene oxide GO and hydrazine hydrate, and after reaction, 3D printing is performed to obtain A-BiOBr / RGO composite materials.

[0012] Step 1) The specific preparation method is:

[0013] The Bi source is dissolved in a mannitol solution, and polyvinyl pyrrolidone is added to obtain solution A; KBr is dissolved in water to obtain solution B; solution B is added to solution A, stirred and mixed, and heated to react to obtain ultrathin BiOBr nanosheets;

[0014] Step 1) The preparation method is as follows: the concentration of the Bi source in the mannitol solution is 0.03-0.05 mol / L; the concentration of the mannitol is 0.1M; the Bi source is Bi(NO3)3·5H2O; the mass ratio of the Bi source to polyvinyl pyrrolidone is 1:0.8-1; polyvinyl pyrrolidone is referred to as PVP; the molar ratio of the Bi source to KBr is 1:0.4-1; the water is deionized water; the concentration of KBr in water is 0.02-0.05 mol / L; the stirring and mixing refers to stirring at a speed of 450r / min for 25 minutes; the heating reaction refers to a hydrothermal reaction at a temperature of 160°C for 3 hours. In the present invention, mannitol has good solubility and stability, and can be used as a solvent or reaction medium to help dissolve other chemical substances and promote the progress of chemical reactions.

[0015] In step 1), after the heating reaction is completed, the mixture is naturally cooled to room temperature, and centrifuged and washed with deionized water and ethanol to remove impurities; after washing and discarding the supernatant, the mixture is dried at 50°C to obtain the obtained product. Further, the dried sample is ground into powder by a mortar to finally obtain ultrathin BiOBr nanosheets. The size of the ultrathin BiOBr nanosheets is 10-90nm.

[0016] In step 2), the mass ratio of ultrathin BiOBr nanosheets to graphene oxide GO is 1:0.08-0.1; the dosage ratio of ultrathin BiOBr nanosheets to hydrazine hydrate is 1:0.5-0.8 g / mL; the reaction is performed for 25-35 min; and graphene oxide is reduced by hydrazine hydrate.

[0017] Preferably, step 2) is: placing ultrathin BiOBr nanosheets in distilled water, ultrasonically dispersing, to obtain a BiOBr nanosheet suspension; adding a GO suspension and hydrazine hydrate, stirring to react; the concentration of the ultrathin BiOBr nanosheets in distilled water is 0.09-1 g / mL; the concentration of the GO suspension is 10 mg / mL; the volume ratio of distilled water, GO suspension and hydrazine hydrate is 11:9:0.6; the stirring reaction refers to a reaction time of 30 minutes.

[0018] In step 2), the 3D printing is performed using a direct writing 3D printer according to the model and parameters to obtain a three-dimensional A-BiOBr / RGO composite material of desired shape and structure. Preferably, the printing is a 25 mm square mesh structure with a mesh aperture of 4 mm.

[0019] Furthermore, in step 2), the printed material is placed in a -20°C environment and frozen for 24 hours to form a stable ice template; and then freeze-dried under vacuum conditions for 48 hours to remove the ice template and form a porous three-dimensional structure to obtain a three-dimensional A-BiOBr / RGO composite material. Preferably, the freeze-drying process is performed using an LGJ-10 freeze dryer.

[0020] The present invention provides a 3D printed integral photocatalytic material, which is prepared by the above method. The 3D printed integral photocatalytic material has a porous structure of 1-100 μm.

[0021] The present invention provides an application of a 3D printed monolithic photocatalytic material for degrading organic pollutants, including the treatment of levofloxacin antibiotics (LEV) and tetracycline (TC) organic pollutants, especially for low-concentration degradation. The degradation concentration range is 500ng / L-10mg / L.

[0022] Furthermore, the application method is: placing the 3D printed monolithic photocatalytic material in an organic pollutant solution, stirring it in the dark, turning on the light, and stirring it;

[0023] Alternatively, the 3D printed monolithic photocatalytic material is loaded onto a polyethersulfone PES membrane using vacuum filtration to form an A-BiOBr / RGO / PES composite membrane, which is used to treat organic pollutants in a flow-type photocatalytic membrane reactor (PMR).

[0024] The flow-type photocatalytic membrane reactor also includes a light source, a reactor and a circulating water system, and is used for treating continuously flowing organic polluted water.

[0025] The present invention prepares a new composite material for photocatalytic degradation of organic pollutants in water, which is particularly suitable for treating wastewater containing antibiotics such as levofloxacin (LEV) and other organic micropollutants, the presence of which in water bodies poses a threat to the environment and public health. By utilizing photocatalytic technology, the present invention aims to provide an efficient and environmentally friendly solution to reduce or eliminate the impact of these harmful pollutants on water bodies. The present invention combines reduced graphene oxide (RGO) with good conductivity to enhance the photocatalytic performance. The present invention develops a new type of A-BiOBr / RGO three-dimensional photocatalyst, which aims to improve the photocatalytic degradation efficiency of organic pollutants such as LEV, and the treatment cost is low. The A-BiOBr / RGO three-dimensional photocatalyst of the present invention combines the photocatalytic activity of bismuth oxybromide with the conductivity and specific surface area advantages of reduced graphene oxide, significantly improves the photocatalytic efficiency, and especially shows excellent performance in the treatment of low-concentration pollutants.

[0026] The technical advantages of the present invention are mainly reflected in the following aspects: 3D printing can quickly prepare photocatalytic materials, realize the macroscopic structure optimization of materials and the precise control of active components, and is conducive to strengthening the mass transfer / heat transfer process in the catalytic process, and is flexible in operation and highly reliable. Efficient photocatalytic performance: By combining the two-dimensional photocatalytic material BiOBr with RGO with good conductivity, a three-dimensional composite structure is formed, which significantly improves the photocatalytic efficiency. This structure not only increases the specific surface area of ​​the material and provides more active sites, but also promotes the separation and transmission of photogenerated charges, thereby improving the rate and efficiency of the photocatalytic reaction. At the same time, it can achieve efficient degradation of nanogram to milligram-level pollutants. Extended light response range: The introduction of RGO enables the A-BiOBr / RGO composite material to effectively absorb visible light and near-infrared light, while BiOBr mainly absorbs ultraviolet light. This complementary light absorption characteristic expands the light response range of the photocatalyst, enabling the photocatalyst to absorb light energy in a wider spectral range, thereby improving the utilization efficiency of solar energy. The present invention also has excellent stability: The A-BiOBr / RGO composite material exhibits good stability, which is crucial for long-term operation and economic benefits in practical applications. Environmentally friendly photocatalytic process: The photocatalytic process of the present invention does not require the addition of external chemical reagents, and only relies on light energy and the characteristics of the catalyst itself to drive the reaction. Therefore, it is an environmentally friendly pollutant treatment technology. Innovative equipment design of the present invention: By integrating the A-BiOBr / RGO composite material with a flow-type photocatalytic membrane reactor (PMR), the present invention provides a new water treatment technology. This design not only improves the removal efficiency of micropollutants, but also simplifies the catalyst recovery process and reduces operating costs. Broad application potential: The A-BiOBr / RGO composite material of the present invention is not only suitable for the photocatalytic degradation of antibiotics such as levofloxacin, but also has the potential to be applied to the treatment of other organic pollutants, such as pesticides, industrial chemicals, etc., and has broad application prospects. Highly efficient micropollutant removal ability. Under ultra-low concentration pollutant conditions, the A-BiOBr / RGO composite material exhibits efficient removal ability, which can meet strict environmental standards and regulatory requirements, and is of great significance for improving water quality and protecting the environment.

[0027] Compared with the prior art, the present invention provides a new type of ultra-thin A-BiOBr / RGO three-dimensional photocatalyst. During the preparation, due to the addition of polyvinyl pyrrolidone (PVP), polyvinyl pyrrolidone (PVP) can be adsorbed on the surface of BiOBr crystals to prevent the growth of crystals, thereby preparing ultra-thin BiOBr nanosheets by a hydrothermal method. It is then compounded with RGO, and a direct-write 3D printer is used to print out an A-BiOBr / RGO composite material of a desired shape and structure according to a predetermined model and parameters, and the composite material is applied to a PES membrane. The composite material exhibits excellent photocatalytic degradation of pollutants (LEV) in water under visible light. The catalyst preparation method is simple and easy to operate, has good stability, is environmentally friendly, and after degradation, the catalyst material can be scraped off the PES membrane, will not flow into the environment, is easy to recycle, and has significant technical advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a flow chart for the preparation of A-BiOBr / RGO composite materials;

[0029] Figure 2 Scanning electron microscope (SEM) images of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites;

[0030] Figure 3 Transmission electron microscopy (TEM) images of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites;

[0031] Figure 4 X-ray diffraction (XRD) patterns of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites;

[0032] Figure 5 UV-visible diffuse reflectance spectra (DRS) of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites;

[0033] Figure 6 Transient photocurrent response diagrams of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composite materials;

[0034] Figure 7 Electrochemical impedance spectroscopy (EIS) of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites;

[0035] Figure 8 The efficiency curves of bulk BiOBr and ultrathin BiOBr materials during the adsorption of levofloxacin (LEV) in dark reaction;

[0036] Fig. 9 The efficiency curves of bulk BiOBr and ultra-thin BiOBr materials in the process of photocatalytic degradation of LEV;

[0037] Fig.10 is the water flux of pure PES membrane and A-BiOBr / RGO / PES membrane before and after photocatalysis;

[0038] Fig.11 The efficiency curve of A-BiOBr / RGO / PES membrane in the continuous flow photocatalytic reactor for degradation of LEV;

[0039] Fig.12 The efficiency curve of A-BiOBr / RGO / PES membrane in the continuous flow photocatalytic reactor for degradation of LEV;

[0040] Fig.13 This is a schematic diagram of 3D printing of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0043] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0044] Comparative Example 1

[0045] A method for preparing a bulk BiOBr photocatalytic material comprises the following steps:

[0046] 1) Preparation of solution A: Weigh 0.97 g (2 mmol) of Bi(NO3)3·5H2O and dissolve it in 40 mL of deionized water to form a Bi source solution;

[0047] 2) Preparation of solution B: Dissolve 0.238 g (2 mmol) of KBr in 40 mL of deionized water to form a salt solution.

[0048] 3) pH adjustment and hydrothermal reaction: The pH value of solution A was adjusted to 1 by dropwise addition of concentrated nitric acid and stirred for 30 minutes; then, solution B was added to solution A, and after mixing, the mixture was transferred to a 100 mL polytetrafluoroethylene autoclave and heated at 140° C. for 24 hours.

[0049] 4) Post-treatment: After the reaction is completed, the autoclave is naturally cooled to room temperature, and the solution after the reaction is transferred to a centrifuge tube for washing; deionized water and ethanol are added, and the centrifuge is washed at a speed of 10,000 rpm for 5 minutes, the supernatant is discarded, and the centrifuge tube is moved to an oven and dried at 50°C. The obtained catalyst is recorded as bulk BiOBr. In the present invention, bulk BiOBr refers to block BiOBr.

[0050] Example 1

[0051] A method for preparing a 3D printed monolithic photocatalytic material comprises the following steps:

[0052] 1) Preparation of Bi source solution: First, 0.97 g (2 mmol) of Bi(NO3)3·5H2O was weighed and dissolved in 60 mL of 0.1 M mannitol aqueous solution to form a high concentration Bi source solution.

[0053] 2) Stirring and adding PVP: The above Bi source solution was placed on a stirrer and the stirring speed was set to 450 r / min. During continuous stirring, 0.8 g of polyvinyl pyrrolidone (PVP, MW: 45000-58000, K30) was gradually added to the solution until it was completely dissolved to obtain a mixed solution containing the Bi source solution and PVP.

[0054] 3) Injection and mixing of salt solution: Dissolve 0.238 g (2 mmol) of KBr in 40 mL of deionized water, and ensure that KBr is completely dissolved to form a uniform solution. Inject the salt solution dropwise into the mixture containing the Bi source solution and PVP through a dropper, and continue to stir at a speed of 450 r / min for 25 minutes to ensure that the components are fully mixed.

[0055] 4) Hydrothermal reaction: The mixed solution in step 3) was transferred to a polytetrafluoroethylene autoclave and subjected to a hydrothermal reaction at 160° C. for 3 hours.

[0056] 5) Post-treatment: After the reaction is completed, the autoclave is allowed to cool naturally to room temperature. The reaction solution is transferred to a 50 mL centrifuge tube and washed with deionized water and ethanol to remove impurities. The washing process uses a centrifugal speed of 10,000 r / min and a centrifugal time of 5 minutes. After washing and discarding the supernatant, the centrifuge tube is placed in an oven and the catalyst is dried at a temperature of 50°C.

[0057] 6) Powder preparation: The dried sample is ground into powder using a mortar until no coarse particles are visible to the naked eye, and finally ultrathin BiOBr nanosheets are obtained.

[0058] 7) Dispersion of nanosheets: First, 1 g of ultrathin BiOBr nanosheets was placed in a beaker containing 11 mL of distilled water, and the mixture was treated with an ultrasonicator to ensure that the nanosheets were evenly dispersed in the distilled water to form a stable BiOBr nanosheet suspension.

[0059] 8) Addition and reaction of GO suspension: 9 mL of 10 mg mL GO was added to the above BiOBr nanosheet suspension. -1 GO suspension was prepared by adding 0.6 mL of hydrazine hydrate and stirring was continued at room temperature for 30 min to promote the reduction of GO and the uniform mixing of BiOBr nanosheets and RGO.

[0060] 9) 3D printing: The mixture obtained in step 8) is transferred to a direct writing 3D printer and printed according to a predetermined model and parameters. Through precise printing control, a three-dimensional A-BiOBr / RGO composite material (i.e., Atomically-thin-BiOBr / RGO) of a desired shape and structure can be obtained. In this experiment, a 25 mm square mesh structure with a mesh aperture of 4 mm is printed.

[0061] 10) Freeze drying: The A-BiOBr / RGO composite material prepared in step 9) was placed in a -20°C environment and frozen for 24 hours to form a stable ice template. Subsequently, a freeze drying process was performed under vacuum conditions using a LGJ-10 freeze dryer for 48 hours to remove the ice template and form a porous three-dimensional structure, thereby obtaining a printed three-dimensional A-BiOBr / RGO composite material.

[0062] 11) Making A-BiOBr / RGO / PES membrane: Using a PES microfiltration membrane with a diameter of 47 mm and a pore size of 0.1 μm, 3D-printed three-dimensional A-BiOBr / RGO composite material of appropriate size was laid on the PES microfiltration membrane. Specifically, the PES membrane was first filtered with 20 ml of polyethylene glycol aqueous solution (polyethylene glycol mass fraction of 25%) using a suction filtration device, and then filtered with 10 ml of glutaraldehyde. Polyethylene glycol and glutaraldehyde act as adhesives. After the filtration, the 3D material was spread on the PES microfiltration membrane to make an A-BiOBr / RGO / PES membrane.

[0063] Figure 1The preparation flow chart of A-BiOBr / RGO composite material is shown, which describes the dissolution and hydrothermal reaction process of Bi(NO3)3·5H2O and KBr, and the combination step of RGO and BiOBr.

[0064] Figure 2 Scanning electron microscope (SEM) images of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites show the microscopic morphology and three-dimensional structural characteristics of the materials. It can be observed that BiOBr nanosheets are evenly distributed on the RGO network, forming a composite with a porous structure; Figure 2 In the figure, a stands for Bulk BiOBr, which refers to bulk BiOBr, which is in block form; b stands for Atomically-thin BiOBr, which refers to ultra-thin BiOBr, which is an accumulation of ultra-thin nanosheets; and c stands for A-BiOBr / RGO, which refers to A-BiOBr / RGO composite material, which is an interconnected porous structure.

[0065] Figure 3 Transmission electron microscopy (TEM) images of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites further confirm the size and thickness of BiOBr nanosheets, as well as their distribution on the RGO substrate.

[0066] Figure 4 X-ray diffraction (XRD) patterns of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites. By comparing with standard cards, the characteristic peaks all correspond to the standard cards, confirming the crystal structure and phase purity of the materials.

[0067] Figure 5 The UV-visible diffuse reflectance spectra (DRS) of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites show that the light absorption region of ultrathin BiOBr is red-shifted compared to that of bulk BiOBr, and the light absorption edge of ultrathin BiOBr is red-shifted from 490nm to 630nm of A-BiOBr / RGO composites, indicating that it has better visible light absorption capacity, can effectively excite electron-hole pairs, and improve photocatalytic performance. The introduction of RGO makes the absorption range wider.

[0068] Figure 6The transient photocurrent response diagrams of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composite materials show that the photocurrent intensity of ultrathin BiOBr is higher than that of bulk BiOBr, which strongly proves that ultrathin BiOBr has a more superior performance in effectively separating photogenerated electron-hole pairs. The introduction of RGO makes the separation efficiency of photogenerated electron-hole pairs higher; the A-BiOBr / RGO composite material shows a higher photocurrent intensity, which indicates that the prepared A-BiOBr / RGO composite material shows a higher efficiency of photogenerated charge separation.

[0069] Figure 7 The electrochemical impedance spectroscopy (EIS) of bulk BiOBr, ultrathin BiOBr, and A-BiOBr / RGO composites shows that the charge transfer resistance of ultrathin BiOBr is significantly lower than that of bulk BiOBr, which indicates that it is faster in carrier transport and has a lower interface charge transfer resistance; the introduction of RGO makes the interface charge transfer resistance smaller. A smaller semicircle diameter means a lower resistance. Compared with bulk and ultrathin, A-BiOBr / RGO composites have a smaller interface charge transfer resistance. Therefore, the charge has a faster transfer speed on the A-BiOBr / RGO composite.

[0070] Example 2

[0071] An application method of ultra-thin BiOBr for degrading levofloxacin (LEV) comprises the following steps:

[0072] 1) Preparation of photocatalyst: Ultrathin BiOBr was prepared according to the method described in Example 1.

[0073] 2) Construction of the photocatalytic reaction system: 15 mg of ultrathin BiOBr was added into a 50 mL simulated pollution solution containing levofloxacin (LEV) at a concentration of 1 mg / L.

[0074] 3) Illumination experiment: The above solution was injected into a 50 mL quartz reaction container and placed in a multi-channel reaction device; the circulating water was turned on and the temperature was set to 30°C. Stirring was carried out in the dark for 30 minutes, and then the xenon lamp was turned on with a light intensity of 200 mW / cm 2 , the speed was adjusted to 400r / min and the reaction time was set to 120 minutes.

[0075] 4) Performance evaluation: After the reaction is completed, the sample is centrifuged to remove particles and the supernatant is taken. The change of the maximum absorption peak at 354 nm is monitored using a UV-visible spectrophotometer to analyze the LEV concentration of the sample at different times.

[0076] A comparative experiment was set up: the same method as in Example 2 was followed, except that the catalytic material was replaced with an equal amount of bulk BiOBr prepared in Comparative Example 1, and the treatment effects of different catalyst materials were compared.

[0077] Example 3

[0078] An application method of an A-BiOBr / RGO / PES membrane for degrading levofloxacin (LEV), comprising the following steps:

[0079] 1) Solution preparation: First, prepare the levofloxacin solution to a concentration of 1 mg / L. This step ensures that the levofloxacin solution used in the experiment has a consistent initial concentration, which facilitates the subsequent photocatalytic degradation efficiency evaluation.

[0080] 2) Double-layer beaker setup: Pour the prepared levofloxacin solution into a double-layer beaker. The design of the double-layer beaker allows for temperature control, and by connecting to cooling circulating water, the temperature of the solution can be kept stable during the experiment.

[0081] 3) Solution circulation: The levofloxacin solution was continuously injected into the photocatalytic membrane reactor (PMR) at a flow rate of 1.260 mL / min using a peristaltic pump. This step ensured the uniform flow of the solution in the reactor, and the residence time of the solution in the reactor could be controlled by adjusting the flow rate of the pump, which was 500 minutes in this experiment.

[0082] 4) Photocatalytic reaction: The light source is placed above the photocatalytic membrane reactor (PMR), facing the quartz glass. The light source is a xenon lamp with a light intensity of 200mW / cm 2 .

[0083] 5) Product collection: The permeate produced during the photocatalytic reaction is collected through a permeation tank. The design of the permeation tank can effectively separate the substances generated by the reaction, which is convenient for subsequent analysis and detection.

[0084] 6) Weight measurement: Use a balance to measure the weight of the permeate. This step can monitor the mass change of the solution during the photocatalytic process and thus evaluate the effect of photocatalytic degradation.

[0085] 7) A photocatalytic membrane reactor was prepared using the A-BiOBr / RGO / PES membrane prepared in Example 1. The membrane was fixed in the reactor to capture and degrade organic pollutants entering the reactor through the mobile phase.

[0086] A comparative experiment was set up: the same method as in Example 3 was followed, except that the A-BiOBr / RGO / PES membrane was replaced with a PES membrane, and the treatment effects of different membranes were compared.

[0087] Figure 81 is the efficiency curve of the bulk BiOBr and the ultra-thin BiOBr material of Example 2 in the process of adsorbing levofloxacin (LEV) under dark reaction; it can be seen that after a certain period of adsorption, the ratio of the pollutant solution concentration to the original concentration. Figure 8 In the test, LEV is a blank test without adding catalyst to exclude the influence of LEV itself on photodegradation.

[0088] Fig. 9 This is the efficiency curve of bulk BiOBr and ultra-thin BiOBr material in Example 2 during the photocatalytic degradation of LEV. After 30 minutes of adsorption in the dark, the light was turned on for 90 minutes. The ratio of the pollutant solution concentration to the original concentration continued to decrease, showing the effect of illumination time on the LEV removal rate.

[0089] Fig.10 The water flux of pure PES membrane and A-BiOBr / RGO / PES membrane in Example 3 before and after photocatalysis shows that the loaded catalyst does not affect the water flux of the membrane; the water flux is the volume of pure water passing through a membrane of a certain area per unit time. The water flux of blank PES membrane and A-BiOBr / RGO / PES membrane before and after degradation in the reactor was tested, which shows that the preparation of A-BiOBr / RGO / PES membrane does not significantly affect the water flux of the PES membrane itself, and after the degradation test, it does not significantly affect the water flux of the PES membrane itself.

[0090] Fig.11 This is the efficiency curve of the A-BiOBr / RGO / PES membrane in Example 3 for degrading LEV in a continuous flow photocatalytic reactor. After a certain volume of pollutant solution passes through, the ratio of the concentration of LEV after degradation to the original concentration of A-BiOBr / RGO / PES membrane and pure PES membrane shows the effect of illumination time on the LEV removal rate. The degradation effect of A-BiOBr / RGO / PES membrane is significantly higher than that of pure PES membrane.

[0091] Fig.12 The figure is the efficiency curve of A-BiOBr / RGO / PES membrane degrading LEV in a continuous flow photocatalytic reactor. By changing the concentration of the pollutant aqueous solution and repeating the experiment, the degradation efficiency at the same time is obtained. The effect of different concentrations on the LEV removal rate is shown, and the degradation concentration range of the present invention is 500ng / L-10mg / L, and the degradation rate is relatively high.

[0092] The present invention compares the effects of bulk BiOBr, ultrathin BiOBr materials and A-BiOBr / RGO / PES film treatment. It can be seen that 3D printed monolithic photocatalytic materials show significant technical advantages in improving photocatalytic efficiency, expanding light response range, enhancing stability, environmental friendliness, innovative equipment design and wide application potential.

[0093] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a 3D printed monolithic photocatalytic material, characterized in that: The preparation method comprises the following steps: 1) Ultrathin BiOBr nanosheets were synthesized by hydrothermal method using polyvinyl pyrrolidone as template; 2) Ultrathin BiOBr nanosheets are mixed with graphene oxide GO and hydrazine hydrate, and after reaction, 3D printing is performed to obtain A-BiOBr / RGO composite materials.

2. The preparation method according to claim 1, characterized in that: Step 1) The specific preparation method is: The Bi source is dissolved in a mannitol solution, and polyvinyl pyrrolidone is added to obtain solution A; KBr is dissolved in water to obtain solution B; solution B is added to solution A, stirred and mixed, and heated to react to obtain ultrathin BiOBr nanosheets.

3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of ultra-thin BiOBr nanosheets to graphene oxide GO is 1:0.08-0.

1.

4. The preparation method according to claim 1 or 3, characterized in that: In step 2), the usage ratio of the ultra-thin BiOBr nanosheets to hydrazine hydrate is 1:0.5-0.8 g / mL.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The reaction in step 2) refers to the reaction time of 25-35 min.

6. The preparation method according to claim 1, characterized in that: Step 2) is: placing the ultra-thin BiOBr nanosheets in distilled water, ultrasonically dispersing them to obtain a BiOBr nanosheet suspension; adding the GO suspension and hydrazine hydrate, and stirring to react.

7. A 3D printed monolithic photocatalytic material prepared by the preparation method according to any one of claims 1 to 6.

8. An application of the 3D printed monolithic photocatalytic material according to claim 7, characterized in that: Used to degrade organic pollutants.

9. The use according to claim 8, characterized in that: The application method is: place the 3D printed integral photocatalytic material in an organic pollutant solution, stir it in the dark, turn on the light, and stir it.

10. The use according to claim 8, characterized in that: The 3D printed monolithic photocatalytic material was loaded onto the polyethersulfone PES membrane by vacuum filtration to form an A-BiOBr / RGO / PES composite membrane, which was used to treat organic pollutants in a flow-type photocatalytic membrane reactor.

Citation Information

Patent Citations

  • Rapid microwave preparation method of bismuth oxybromide photocatalyst

    CN116251627A

Cited By

  • Graphene quantum dot regulated bismuth oxybromide photocatalytic material as well as preparation method and application thereof

    CN120695852A